Prevalence of cardiovascular risk factors among patients with polycystic ovarian syndrome (PCOS) in Erbil city - Mohammed Saleh , Nishtiman; Baha`addin Ahmed , Yousif (Diyala Journal of Medicine, 2021)
Background: Polycystic ovarian syndrome is a common endocrine disorder of women during reproductive age, associated with increased risk of cardiometabolic diseases. Objective: To assess the prevalence of cardiovascular risk factors in patients with the polycystic ovarian syndrome in comparison to age-matched control. Patients and Methods: This cross-sectional studyis conducted in Erbil city fromSeptember 2020 to January 2021. It included 40 cases of polycystic ovarian syndrome and 40 cases of healthy controls. Participants underwent detailed history, physical examination. Laboratory investigations (blood sugar, lipid profile, serum testosterone and serum prolactin) and pelvic ultrasound were done for them. Data analysis was performed by Statistical Package for Social Sciences (SPSS) version 25. Results: Women with the polycystic ovarian syndrome have a higher proportion to obesity, abnormal blood sugar, and dyslipidemia, they have higher rate of menstrual irregularity, hyperandrogenic state and hirsutism, than age-matched control. The risk for hypertension remains the same for both PCOS and the control group. Conclusion: The proportion of obesity, diabetes, and dyslipidemia is higher in Polycystic ovarian syndrome than the control group.